The diurnal pattern of cytokines, chemokines and growth factors in human saliva—a pilot study - Jasim, Hajer; Ghafouri, Bijar; Ernberg, Malin (Frontiers in Dental Medicine, 2024)
Background: Understanding of possible periodicity of cytokines, chemokines and growth factors is of great interest and provide valuable information for research into pathophysiological mechanism of inflammatory disease and chronic pain. Significant efforts have been made to identify different analytes in saliva. For precision and accuracy in measurement and interpretation of results, it is crucial to know the source of variability, especially the circadian variation for the analytes. Objective: The study aimed to analyze circadian variation in 71 inflammatory markers in both unstimulated and stimulated saliva, as well as plasma, from a sample of healthy individuals. Methods: Ten young adults participated. Unstimulated and stimulated whole saliva were collected at 3-hour intervals between between 7:30 am and 7:30 pm. Blood samples were drawn in connection with the first and last saliva collection. All samples were analyzed using the U-PLEX 71-Plex assay. Results: The analysis showed distinct clustering of the 71 inflammatory mediators between plasma and saliva. Furthermore, differences were also observed between stimulated and unstimulated saliva. The proteins were clustered into three groups that expressed different circadian rhythms. These clusters were stable over time in stimulated saliva but showed significant variability in unstimulated saliva (P < 0.05). Conclusions: These results suggest that time of the day could influence the detection and interpretation of inflammatory markers and collecting saliva samples at consistent times across participants will help control for the natural fluctuations in salivary composition. The results encourage further exploration of salivary diagnostics, particularly in understanding circadian rhythms and localized immune responses.